Peran Solidaritas Karyawan Pada Keinginan Keluar dan Kelelahan Bekerja: Pemediasi Kepuasan Kerja - Sunyoto, Danang; Rohmah, Tri Nur; Budiherwanto, Iwan (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2024)
Goal–The Role of Employee Solidarity on Intention to Leave and Work Burnout: Mediator of Job Satisfaction. Design / Methodology / Approach – Research uses a saturated population or sample of all Indomaret Franchise Shop employees in Kulon Progo. Data collection methods using questionnaires and observation. The data analysis method uses descriptive qualitative and quantitative. Research Results–Employee Solidarity and job satisfaction play a significant role in Job Satisfaction and work fatigue. On the other hand, employee solidarity does not play a role in the desire to leave and work fatigue, nor does job satisfaction play a role in the desire to leave. Then job satisfaction is not a mediation between employee solidarity and desire to leave, but job satisfaction plays a mediating role between employee solidarity and work fatigue.